BSFL biodiesel production and cost reduction: A review - Lingfeng He; Abdullah Amru Indera Luthfi; Noorashikin Md Saleh; Zahira Yaakob; Nor Sakinah Mohd Said; Peer Mohamed; Xiaoling Li (Fuel Processing Technology)
The international community's demand for gasoline is also expanding. This huge demand has also led to energy shortages. Gasoline combustion is characterized by easy acid rain, high organic compound content, and pungent smell and color. It threatens aquatic life, human health and the environment. Therefore, there is an urgent desire to find suitable ways to produce fuel oil that will allow it to reach its previous environmental limits. Recognizing the importance of green technologies and sustainable development, the United Nations launched a forward-looking plan called the Sustainable Development Goals, which are implemented by countries around the world to ensure a better future tomorrow. This manuscript provides an overview of black soldier fly larva processing and biodiesel, its production, conventional handling, and current practices. The integrated system includes light parameter optimization, carbon dioxide optimization, and cost reduction to treat specific microalgae in their respective water bodies.